KAWASAN KAMPUNG BATIK KAUMAN SEBAGAI SUMBER PEMBELAJARAN IPS DI SMP - Mukti Wijaya, Yahya Restu; Sariyatun, Sariyatun; Isawati, Isawati (Program Studi Pendidikan Sejarah FKIP Unversitas Sebelas Maret, 2016)
The purpose of this study was to know: (1) historical description of Village Batik Kauman Surakarta, (2) potential of Village Batik Kauman as a source of learning social studies/history in the curriculum of 2013, (3) relevance of Village Batik Kauman with KI and KD History social studies.This study used a qualitative descriptive method that examines the events at the present time by generating descriptive data in the form of words written or spoken of certain persons or behaviors that can be observed by using certain measures. In this study used a single-rooted strategy case studies that target to be studied has been limited and determined, and focused on a single location has its own characteristics. Source of data used is the source of objects, places, events, informants, and documents. Data collected by observation, interviews, and document analysis. The sampling technique used was purposive and snowball sampling. This study, to search for the validity of the data used two techniques namely data triangulation triangulation and triangulation methods. The data analysis technique used is interactive analysis, the analysis process that moves between the three components which include data reduction, data presentation, and verification/conclusion.Based on the results of this study concluded: (1) The history of Village Batik Kauman have close links with Keraton Kasunanan Hadiningrat Surakarta. Kauman stand together with the establishment of the Great Mosque Keraton as a religious center during the PB III. Kauman is the abdi dalem religious field and students. The wife of the abdi dalem were given the royal batik training continues cultivated until now. (2) Village Batik Kauman has potential as a source of social studies learning. Culture and ancient buildings in Kauman can be used as a source of learning, among others, the Great Mosque, Mosque Sesemen, ancient houses, batik skills, and multicultural society. (3) The relevance of Village Batik Kauman as a source of social lesson contained in the Basic Competence understand changes in Indonesian society during the pre post period, the Hindu-Buddhist, and Islamic period in the geographical aspects, economics, culture, education and politics .